Training of the Health Promotion Basis of Junior Teenagers in The Extracurricular Activity System - Hennadii Kovalchuk (Pedagogical Discourse, 2014)
The paper makes an attempt to discover the process of training of health promotion basis of junior teenagers in the extracurricular activity system. The various forms and methods of the off-time job that are directed to the health saving and strengthening are based on the author` s investigation on the assumption of the development peculiarities of schoolchildren of the given age period and theirs needs in self-knowledge, self-education and self-assertion. The special attention is paid to the usage of active methods that are directed to the formation of positive motivation of teenagers, the realization of activity significance, the equipment with a system of knowledge, skills and abilities of health improvement, necessity of control realization and corrective actions to own lifestyle.